620. Real-World Insights on HIV Treatment Decision-Making in Federal and Public Healthcare Settings. (31st December 2020) - Okulicz, Jason F; Zawitz, Chad J; Blaylock, Jason M; Taneva, Ekaterina S; Simone, Laura; Carter, Jeffrey; Sapir, Tamar
Abstract: Background: Evidence-based guidelines and novel antiretroviral therapies (ART) for people living with HIV (PLHIV) are quickly evolving. Understanding the practice patterns, gaps, and needs of healthcare professionals (HCPs) who care for PLHIV in specific settings, such as those in the federal and public healthcare sector, can inform education and improvement strategies. Methods: Surveys were administered before and after a series of 1.5 hour continuing education programs (n=20) on HIV treatment conducted live in various US cities between April 2019 and March 2020. These programs were designed for HCPs in federal and public healthcare systems, such as the Veterans Affairs Medical Centers, Military Medical Treatment Facilities, and Federally Qualified Health Centers. Results: Survey respondents (n=655) were mostly physicians (35%) or nurse practitioners/physician assistants (25%) practicing in federal healthcare settings (Table 1). Respondents reported a mean patient volume of 1, 893 (±240) PLHIV monthly. Before and after the education, only 34% and 61% of HCPs, respectively, correctly identified recommended first-line ART for most PLHIV. Only 19% and 38% of HCPs reported high levels of confidence in selecting ART for rapid ART initiation before and after the education. A case-based survey item showed that 35% (pre-education) and 45% (post-education) of HCPs would recommend switching a virologically suppressed patient over age 50 with comorbidities from a boosted protease inhibitor-based regimen to an integrase inhibitor-based regimen. Only 13% and 33% of HCPs reported high confidence in switching ART for older patients with comorbidities before and after the education, respectively. The biggest challenges identified by HCPs were related to ART selection and patient management (Table 1). After the education, HCPs reported needs and intention to improve their team-based processes to: 1) facilitate rapid ART initiation; 2) optimize ART for patients with comorbidities; 3) optimize treatment for patients with virologic failure. Conclusion: This educational program improved knowledge and competency in evidence-based HIV treatment and supported team-based action planning. The findings also inform persistent challenges and needs among HCPs in federal settings. Disclosures: Chad J. Zawitz, MD, Gilead Sciences (Speaker's Bureau)ViiV (Advisor or Review Panel member) Tamar Sapir, PhD, Gilead Sciences, Inc. (Other Financial or Material Support, Independent medical education grant)ViiV Healthcare (Other Financial or Material Support, Independent medical education grant)